Online Criminal Record Monitoring System for Issuance Certificates of Good Conduct, Life, and Morals in Bukavu - Lukendo David, Omari (Tech-E, 2024)
In the Democratic Republic of the Congo, the Ministry of Justice maintains criminal records for individuals with legal antecedents. However, certificates of good conduct, life, and morals are issued by local or district authorities without prior verification of the applicant's criminal record. This is due to the lack of a shared information system between the Ministry of Justice and these authorities. This paper describes the implementation of a platform that allows the Ministry of Justice to share criminal record information with local and district authorities. The system was modeled using the UP7 methodology and the Unified Modeling Language (UML). This platform ensures the reliability of the information provided on certificates of good conduct, life, and morals. Thanks to this new system, anyone with a criminal record is no longer able to hide their past by obtaining a certificate of good conduct, life, and morals that does not mention their criminal record. The results of the tests confirm that the system is user-friendly and meets the requirements of the users.